SENYAWA ISLAM DAN BUDAYA PESISIR SELATAN TULUNGAGUNG - Kabir, Gedong Maulana (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2018)
Islam is always intertwined with local culture. Islam itself has a set of grounds (propositions) that are possible interpreted in harmony with local culture, and vice versa while local culture has taken a root in people's awareness. It could be that the local culture takes root deeper than religious teachings, in the context Islam. Local culture becomes increasingly complex if it associates with a set of community beliefs for the mystique of the southern coastal region of the Java sea, Tulungagung. Relation complex between Islam and the socio-cultural community of the south coast will be examined in this article. The perspective of mystical synthesis will be used in analyzing data from interview results by exploring facts of Tulungagung's south coast community and data from the literature study. This article attempts to explain social-cultural-religious facts that develop in coastal communities south of Tulungagung. In fact, society can create harmony life while maintaining local culture and religious life. This is what might be called Islam mystic synthesis of the south coast.Keywords: Islam, Local Culture, South Coast, Social. Islam selalu berjalin-kelindan dengan budaya lokal. Pada dirinya sendiri, Islam memiliki seperangkat dasar (dalil) yang mungkin ditafsirkan selaras dengan budaya lokal, maupun sebaliknya. Disaat yang sama, budaya lokal telah mengakar dalam kesadaran masyarakat. Bisa jadi budaya lokal mengakar lebih dalam dibandingkan dengan ajaran agama, dalam konteks ini Islam. Budaya lokal menjadi semakin kompleks jika dikaitkan dengan seperangkat keyakinan masyarakat atas mistisitas wilayah pesisir selatan laut Jawa, Tulungagung. Relasi kompleks antara Islam dan sosio-kultural masyarakat pesisir selatan inilah yang akan dikaji dalam artikel ini. Perspektif sintesis mistik akan digunakan dalam menganalisa data dari hasil wawancara yang menelusuri fakta masyarakat pesisir selatan Tulungagung dan data dari penghampiran kajian kepustakaan. Artikel ini berupaya menjelaskan fakta sosial-budaya-keagamaan yang berkembang di masyarakat pesisir selatan Tulungagung. Faktanya, masyarakat bisa menciptakan kehidupan harmoni dengan tetap mempertahankan budaya lokal dan kehidupan keagamaan. Inilah yang, bisa jadi, disebut sebagai Islam sintesis mistik pesisir selatan.Kata kunci: Islam, Budaya Lokal, Pesisir Selatan, Sosial.